Use of Augmented Reality, Gamification and M-learning (2019)
Augmented reality, gamification and M-learning occupy an important place in education today, given the advantages that the use of mobile technologies has brought, independently or in combination with other technological scenarios and different devices that affect the teaching and learning of the different disciplines or that serve as a bridge for improvements to various processes mediated by ICT in teaching and / or learning. In this sense, the article presented here shows an analytical study that was developed under an exploratory, descriptive, interpretative methodology of the categories augmented reality, gamification, and m-learning, based on a characterization in the databases, carried out an exploratory review in the main databases such as ScienceDirect, Scopus and web Science, obtaining 100 reference articles. In this way, it was found that these three categories determined as teaching strategies significantly influence motivation, interest in knowledge, retention and understanding of information for the development of teaching-learning processes. The method used allowed to develop the description of the panorama or superficial knowledge about the use of augmented reality, m-learning, and gamification in basic, secondary and higher education.